Design of memory controllers and input/output controller for low-voltage asynchronous digital signal processor - Low, Joshua Yung Lih. (2009)
This project encompasses the generation of memory blocks, design and implementation of memory and input/output (IO) controllers for a low voltage (1.25V) asynchronous DSP56002 design. DSP56002, from the DSP56K Family, is Motorola’s series of 24-bit general purpose Digital Signal Processor.